Use and Impact of Pessary, Cerclage, and Progesterone for the Secondary Prevention of Preterm Birth: Data from the German Neonatal Network - Hanke, Kathrin; Fortmann, Mats Ingmar; Auerswald, Gesa Henrike; Härtel, Christoph; Olbertz, Dirk; Roll, Claudia; Grüttner, Berthold; Wieg, Christian; Breunig, Stephanie; Rody, Achim; Felderhoff-Müser, Ursula; Herting, Egbert; Göpel, Wolfgang; Bossung, Verena (Zeitschrift für Geburtshilfe und Neonatologie, 2024)
Background To evaluate the use and effect of cervical stitch cerclage, pessary, and progesterone on pregnancy outcome in mothers of very low birth weight infants (VLBWI) born<32 weeks of gestation in the German Neonatal Network (GNN).Methods The GNN is a population-based cohort study enrolling VLBWI since 2009. We included 575 neonates from 424 mothers into our analysis, who were born between 2015 and 2019, after prenatal intervention with cerclage, pessary, progesterone or a combination between 20/0 to 25/0 weeks of gestation to prevent preterm birth. Median intervention-to-birth interval was the primary endpoint.Results 231 of 424 pregnant women had a cerclage only (54.5%), 76 women a pessary only (17.9%), and 27 were prescribed progesterone only (15.3%). The most common combination treatment (>1 intervention group) was cerclage plus progesterone (n=27), followed by cerclage plus pessary (n=13). The median intervention-to-birth interval for the whole cohort was 24 days (IQR 19.0 days). The earlier the intervention was started, the longer the intervention-to-birth interval lasted: When started at 20 weeks, the interval was 34 days in contrast to 11.5 days, when started at 25 weeks. The >1 group was born at a significantly higher median GA with 27.0 weeks (IQR 2.9 weeks) and a higher median birth weight of 980 g (IQR 394 g) accordingly.Conclusion We propose that the earliest possible start of intervention leads to the most efficient pregnancy prolongation.
Keywords: Secondary prevention; Preterm birth; Impact on prologation